Efficacy of Physiotherapy Interventions on Weaning in Mechanically Ventilated Critically Ill Patients: A Systematic Review and Meta-Analysis - Lorenzo Lippi; Lorenzo Lippi; Alessandro de Sire; Francesco D’Abrosca; Biagio Polla; Nicola Marotta; Luigi Mario Castello; Luigi Mario Castello; Antonio Ammendolia; Claudio Molinari; Marco Invernizzi; Marco Invernizzi (Frontiers in Medicine, 2022)
Mechanical ventilation (MV) is currently considered a life-saving intervention. However, growing evidence highlighted that prolonged MV significantly affects functional outcomes and length of stay. In this scenario, controversies are still open about the optimal rehabilitation strategies for improving MV duration in ICU patients. In addition, the efficacy of physiotherapy interventions in critical ill patients without positive history of chronic respiratory conditions is still debated. Therefore, this systematic review of randomized controlled trials (RCTs) with meta-analysis aimed at characterizing the efficacy of a comprehensive physiotherapy intervention in critically ill patients. PubMed, Scopus, and Web of Science databases were systematically searched up to October 22, 2021 to identify RCTs assessing acute patients mechanical ventilated in ICU setting undergoing a rehabilitative intervention. The primary outcomes were MV duration, extubation, and weaning time. The secondary outcomes were weaning successful rate, respiratory function, ICU discharge rate and length of stay. Out of 2503 records, 12 studies were included in the present work. The meta-analysis performed in 6 RCTs showed a significant improvement in terms of MV duration (overall effect size: −3.23 days; 95% CI = −5.79, −0.67, p = 0.01; Z = 2.47) in patients treated with a comprehensive physiotherapy intervention including early mobilization, positioning, airway clearance techniques, lung expansion and respiratory muscle training. The quality assessment underlined 9 studies (75%) of good quality and 3 studies of fair quality according to the PEDro scale. In conclusion, our results provided previously unavailable data about the role of comprehensive physiotherapy intervention in improving MV duration in critical ill patients without chronic respiratory conditions. Further studies are needed to better characterize the optimal combination of rehabilitation strategies enhancing the improvements in critical ill patients without chronic respiratory disorders.